2019
DOI: 10.1177/1469066718799992
|View full text |Cite
|
Sign up to set email alerts
|

Relative quantitation of phosphatidylcholines with interfered masses of protonated and sodiated molecules by tandem and Fourier-transform ion cyclotron resonance mass spectrometry

Abstract: The present work deals with deconvolution of interfered peaks of protonated and sodiated phosphatidylcholines to solve the problem of relative quantitation of these compounds. The method was developed based on the fact that adducts of phosphatidylcholines with proton and sodium ion give unique characteristic peaks in tandem mass spectrometry. Ultrahigh-resolution Fourier-transform ion cyclotron resonance mass spectrometry was used to resolve interfered peaks and thus validate the results of tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…MS analysis of tissue samples is performed on Maxis Impact qTOF (Bruker Daltonics, Bremen, Germany) with the in-lab designed ion source for tissue spray MS [28]. A mixture of H 2 O/methanol 1/9 with 0.1% formic acid is used for online tissue extraction and following spraying [30,31]. The solvent is supplied to the tissue with a flow rate of 1 mL/min by Dionex binary pump (Thermo Scientific, Germering, Germany).…”
Section: Tissue Spray Mass Spectrometry Of Breast Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…MS analysis of tissue samples is performed on Maxis Impact qTOF (Bruker Daltonics, Bremen, Germany) with the in-lab designed ion source for tissue spray MS [28]. A mixture of H 2 O/methanol 1/9 with 0.1% formic acid is used for online tissue extraction and following spraying [30,31]. The solvent is supplied to the tissue with a flow rate of 1 mL/min by Dionex binary pump (Thermo Scientific, Germering, Germany).…”
Section: Tissue Spray Mass Spectrometry Of Breast Samplesmentioning
confidence: 99%
“…Lipid peaks are typically dominated in tissue spray mass spectra [24][25][26], therefore, R-scripts generating theoretical lipid masses are developed to identify the obtained spectra. The possibility of ion formation by protons, sodium cation or potassium cation attachment in the positive ion mode is considered [29][30][31][32]. Deprotonation and chloride anion attachment are considered in the negative ion mode.…”
Section: Tissue Spray Ms Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Shotgun lipidomics based on electrospray ionization mass spectrometry (ESI-MS) allows deep molecular profiling of a sample without significant losses of chemical information [26,27]. The high diagnostic potential of lipidomics has been shown in many areas of medicine, particularly in oncology: lung, thyroid gland, breast, stomach, pancreas, colorectal, liver, kidney, prostate, ovarian, and endometrium cancer [28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][51][31][32][33][34][35][36][37]. MS studies of lipid profiles in tissues and blood plasma have revealed new promising biomarkers of endometriosis (benign gynecological disorder) [26,27,32,33,37,44,47].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are biologically active compounds that regulate a number of important cellular processes, incuding proliferation, apoptosis, and angiogenesis 8 . Differences in the lipid pro le of a tissue allow the identi cation of benign and malignant processes in the tissue [9][10][11][12][13][14][15] . High performance liquid chromatography combined with mass spectrometry (HPLC-MS) is regarded to be the most informative method for lipid analysis 16 .…”
Section: Introductionmentioning
confidence: 99%